Foreign exchange prediction and trading using nature-inspired techniques - Ng, Kai Boon (2017)
Foreign exchange(Forex) is a market where the currencies over the world are traded, it involves a huge monetary value and it concerns people as currencies are needed to be converted for trading and other investment purposes. Over the years, many algorithms are explored to find the most accurate prediction for forex. However, none of the algorithm are proven the best and most accurate for the use of forex prediction. Hence, this project will design a software (MATLAB) which will be able to predict the forex values using one of the nature-inspired technique, Genetic Algorithm(GA), in comparison with the actual value to determine the accuracy of the algorithm. The result obtained will then be compared to past study.